The prosocial behaviors and the disposition to the economic contribution in the visitors of the Cotopaxi National Park, Ecuador - Mantilla Falcón, Marcelo (2022)
Recreational activity in natural areas is of great importance in modern times, but its economic sustainability presents serious difficulties and limitations. One way to ensure its care and conservation is through voluntary contributions from visitors, since the State's contributions are not enough. This study analyzes the possible scenarios to obtain economic funds for the financial sustainability of the Cotopaxi National Park in Ecuador, through a quasi-experiment where 407 national and international tourists participated randomly classified into three groups: reciprocity, conformity and anonymity, framed in what is known as prosocial behaviors. The research was carried out in situ at 4800 meters above sea level. A duly validated survey with dichotomous and multiple-choice questions was applied. The most evident results show that foreign tourists are more willing and willing to collaborate in a range higher than US $ 5.00. It is concluded that an adequate solution to guarantee the care and conservation of natural areas is through voluntary contributions from visitors because state budgets will always be a constraint. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/1602